The Roles of Accelerated Pavement Testing in Pavement Sustainability Engineering, Environment, and Economics - Aguiar-Moya, José P.; Vargas-Nordcbeck, Adriana; Leiva-Villacorta, Fabricio; Loría-Salazar, Luis G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This compendium gathers the latest advances in the area of Accelerated Pavement Testing (APT), a means of testing full-scale pavement construction in an accelerated manner for structural deterioration in a very short term. Compiling novel research results presented at the 5th International Conference on Accelerated Pavement Testing, San Jose, Costa Rica, the volume serves as a timely and highly relevant resource for materials scientists and engineers interested in determining the performance of a pavement structure during its service life (10+ years) in a few weeks or months. Stands as the only collection focusing on the advancements of full scale testing in pavements, and the benefits associated with the technology; Includes the perspective from research programs worldwide that are using the APT technology; Illustrates efficient means of calibrating / developing pavement design methods; Demonstrates the long term savings resulting from evaluating technologies prior to field construction.
Keywords: Materials -- Analysis; Transportation engineering; Traffic engineering; Engineering geology; Characterization and Analytical Technique; Transportation Technology and Traffic Engineering; Geoengineering